Phytoassessment of acid mine drainage: Lemna gibba bioassay and diatom community structure - Gerhardt, A.
An integrated multilevel phytoassessment of an acid mine drainage (AMD, pH range 3.3-6.8) in southern Portugal was performed. A 7-day phytotoxicity bioassay with the duckweed Lemna gibba (chlorosis, necrosis, growth) was carried out, both in the laboratory and in situ, combined with an analysis of the resident epilithic diatom community. The toxicity test was performed with water from the AMD gradient, an unpolluted river control and acidified control water, in order to discriminate potential pH-effects from combined pH- and metal-effects. Diatom communities discriminated well among the sites (alkalophilic species versus halobiontic, acidobiontic and acidophilic species), showing inter-site differences to be larger than intra-site seasonal variations. In L. gibba exposed to AMD, necrosis and growth inhibition were higher in situ compared to the laboratory experiments. L. gibba was more sensitive to AMD than to acidified water. Already after 4 days, growth rate inhibition in L. gibba proved to be a reliable indicator of AMD-stress. Ecotoxicological thresholds obtained with L. gibba corresponded with those obtained previously with animals of intermediate tolerance to AMD. The results were summarised in a multimetric index.